Olfactory memory in mild cognitive impairment and Alzheimer’s disease - Audronyte, Egle; Sutnikiene, Vaiva; Pakulaite-Kazliene, Gyte; Kaubrys, Gintaras (Frontiers in Neurology, 2023)
Introduction: Olfaction is impaired in Alzheimer’s disease (AD). However, olfactory memory has rarely been examined. As the pathogenesis of AD remains largely unknown, collecting more data regarding the occurrence and progression of its symptoms would help gain more insight into the disease. Objective: To investigate olfactory memory and its relationship with verbal memory and other clinical features in patients with early-stage AD. Methods: Three groups of participants were enrolled in this study: patients with mild dementia due to AD (MD-AD, N=30), patients with mild cognitive impairment due to AD (MCI-AD, N=30), and cognitively normal older participants (CN, N=30). All participants underwent cognitive evaluation (Clinical Dementia Rating scale, Mini Mental State Examination, Alzheimer’s Disease Assessment Scale–Cognitive Subscale, delayed verbal recall, and verbal fluency tests) and assessment of olfactory immediate and delayed recognition memory. Results: Olfactory immediate and delayed recognition memory scores were significantly lower in the MD-AD group than in the MCI-AD and CN groups. The MCI-AD and CN groups did not differ significantly (in both cases, Kruskal–Wallis test, p < 0.05; post hoc analysis revealed significant differences between the MD-AD and MCI-AD groups and between the MD-AD and CN groups [p < 0.05], and no significant difference between the MCI-AD and CN groups [p > 0.05]). Verbal immediate recall, delayed recall after 5 minutes, and delayed recall after 30 minutes scores were significantly worse in the MD-AD and MCI-AD groups than in the CN group. MD-AD and MCI-AD groups did not differ significantly (in all cases Kruskal–Wallis test, p < 0.05; post hoc analysis revealed significant differences between MD-AD and CN groups, and MCI-AD and CN groups [p < 0.05] and no significant difference between MD-AD and MCI-AD groups [p > 0.05]). Duration of AD symptoms was a strong predictor of both immediate and delayed olfactory recognition memory scores. Conclusion: Olfactory memory impairment was observed in patients with AD. The changes progress during the course of the disease. However, unlike verbal memory, olfactory memory is not significantly impaired in the prodromal stage of AD.